2019
DOI: 10.1002/jbm4.10126
|View full text |Cite
|
Sign up to set email alerts
|

Bone as a Preferential Site for Metastasis

Abstract: Bone marrow provides a unique microenvironment favoring the colonization and outgrowth of metastatic tumor cells. Despite the high incidence of bone metastasis in breast and prostate cancer patients, many of the molecular mechanisms controlling metastatic progression remain unclear. Several gene signatures associated with bone metastasis have been reported, but no metastasis‐specific gene alterations have been identified. Therefore, there has been considerable interest in understanding how the bone microenviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 174 publications
1
53
0
Order By: Relevance
“…The bone microenvironment regulates complex and relevant processes such as hematopoiesis, osteogenesis and osteolysis [1]. Various studies demonstrated that different molecular mechanisms are involved in promoting cancer cells residency in bone through chemotaxis in bone niches [25]. Most bone metastases occur when prostate, breast and lung primary tumors spread to the bone [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The bone microenvironment regulates complex and relevant processes such as hematopoiesis, osteogenesis and osteolysis [1]. Various studies demonstrated that different molecular mechanisms are involved in promoting cancer cells residency in bone through chemotaxis in bone niches [25]. Most bone metastases occur when prostate, breast and lung primary tumors spread to the bone [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Dormancy induction of bone‐metastasizing prostate cancer cells represents a typical case of MME‐regulated dormancy at a specific organ site. TGFβ2, 181 bone morphogenetic proteins (BMP) 182 and other factors 183 induce dormancy of prostate cancer cells in the bone. The mechanism underlying this site‐specific dormancy is an alteration in the ERK and p38 MAPK signaling ratio so as to create a high p38 and a low ERK signaling 184 .…”
Section: Dormancy Of Disseminating Tumor Cells At Site‐specific Mmesmentioning
confidence: 99%
“…produced by osteoblasts, stored in bone matrix, and released during physiological bone disruption becoming bioavailable for cancer cells ( Florencio-Silva et al, 2015 ; Owen and Parker, 2019 ). In addition, the primary tumor sends systemic signals to set and prepare suitable soil for the metastasis, the so called premetastatic niche (PMN), where stromal cells are also recruited to host cancer cells ( Owen and Parker, 2019 ; Sowder and Johnson, 2019 ).…”
Section: Introductionmentioning
confidence: 99%